A rare earth metal-containing porous core-shell nanosphere and preparation method thereof
The Ce element-enriched trimetal nanospheres were formed by a one-pot multi-step synthesis method, and calcined as a self-template, which solved the problem of cumbersome steps and low yields in the prior art, and achieved the improvement of the regularity and catalytic performance of the nanospheres.
Patent Information
- Application Number
- CN202211348075.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-10-31
AI Technical Summary
The existing core-shell nanomaterial preparation technology has problems such as cumbersome steps, high environmental pollution and low yield, making it difficult to achieve large-scale production and efficient catalysis.
By using a one-pot multi-step synthesis method, the reaction of organic ligand HL10 with rare earth metal salt and transition metal salt is formed to form a trimetal nanosphere enriched with Ce element, and calcined it as a self-template to obtain multi-component porous core-shell nanospheres containing rare earth metals.
The nanospheres have achieved a more regular and uniform morphology and size, forming a multi-component porous core-shell structure, with good electrocatalytic properties, and are suitable for fuel cells and other applications.
Smart Images

Figure CN115889800B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano materials, and in particular relates to a porous core-shell nanosphere containing rare earth metals and a preparation method thereof. Background Art
[0002] Multi-metal core-shell nanomaterials can effectively promote electron transfer between the core and the shell due to the cavity volume between the core and the shell, adjustable metal ratio, more exposed surface catalytic sites and synergistic effects between different substances. Their excellent structural characteristics and catalytic performance make them widely used in many fields such as catalysis, energy, sensors, and medicine.
[0003] At present, many strategies for constructing core-shell structures have been developed, such as template method, electroplating method, etc. Among them, the template method mainly includes hard template method, soft template method and self-template method. The hard template method uses solid particles of a certain shape as templates to prepare core-shell nanomaterials. The soft template method does not use solid particles with fixed shape and size as templates, but selects templates such as microemulsion droplets, surfactant micelles, bubbles, microcapsules, macromolecular aggregates, bacteria, etc., which omits the template synthesis step. The hard template method and the soft template method are limited in large-scale production due to their shortcomings such as cumbersome steps, difficult post-processing, high environmental pollution, and low yield.
[0004] In the process of constructing nanostructures, the self-template method refers to the use of nanomaterials themselves as templates to synthesize nanomaterials with special structures. It mainly includes two steps: the first step is the preparation of template nanomaterials, and the second step involves the chemical conversion of templates into special structures. The self-template method has attracted widespread attention due to its advantages of green and environmentally friendly synthesis process, simple experiments and operations, fast reaction rate, and high yield. In addition, the literature "Low-Temperature COOxidationover CeO2 and CeO2@Co3O4 Core-Shell Microspheres, New J. Chem, 2017, 41, 13418–13424" reported the synthesis of pure cerium dioxide core-shell spheres by simple self-template and calcination methods. This method used a one-pot multi-step method for the first time to synthesize tri-metal nanospheres enriched with internal Ce elements and used them as self-templates for calcination. After calcination, a multi-component porous core-shell nanosphere containing rare earth metals was obtained. Compared with other existing technologies for preparing core-shell structures, the entire synthesis process is green and environmentally friendly, the experiment and operation are simple, the reaction rate is fast, and the yield is high. Summary of the invention
[0005] In order to solve the above-mentioned technical problems, the present invention provides a method for preparing porous core-shell nanospheres containing rare earth metals, comprising the following steps:
[0006] S1: After dissolving the organic ligand, heat to 60°C-70°C, add the rare earth metal salt solution, and react for 0.5h-2h to obtain a primary reaction solution; the structural formula of the organic ligand is as follows:
[0007]
[0008] S2: adding a transition metal salt solution to the primary reaction solution and reacting for 0.5 h to 2 h to obtain a secondary reaction solution;
[0009] S3: adding a transition metal salt solution to the primary reaction solution and reacting for 12 h to 14 h to obtain a tertiary reaction solution;
[0010] S4: calcining the tertiary reaction solutions to obtain the rare earth metal-containing porous core-shell nanospheres.
[0011] First, the unique one-pot multi-step synthesis method obtained the phenomenon of Ce element enrichment inside the nanospheres, which is conducive to the formation of the subsequent multi-component core-shell structure; and the organic ligand HL 10 The decomposition of Co x and H2O gas, which can explain the porous structure formed after calcination. In addition, this special multi-component porous core-shell nanosphere can only be formed when the metal ratio in the precursor is in the appropriate ratio range, which may be due to the different metal contents in the precursor causing different changes in its structure after calcination.
[0012] Preferably, the rare earth metal salt in the rare earth metal salt solution is cerium acetate (Ce(OAc)3) or gadolinium acetate (Gd(OAc)3).
[0013] Preferably, in step S2 or S3, the transition metal salt in the transition metal salt solution is one or more of ferrous acetate (Fe(OAc)2), cupric acetate (Cu(OAc)2), manganese acetate (Mn(OAc)2), zinc acetate (Zn(OAc)2) and cobalt acetate (Ce(OAc)2).
[0014] Furthermore, the rare earth metal salt is cerium acetate; and the transition metal salt is cobalt acetate or manganese acetate.
[0015] Specifically, the rare earth metal salt added for the first time is cerium acetate, the transition metal salt added for the second time is manganese acetate, and the transition metal salt added for the third time is cobalt acetate.
[0016] Preferably, the molar ratio of the organic ligand to the rare earth metal salt in the rare earth metal salt solution is 3-36:1.
[0017] Specifically, the molar ratio of the organic ligand to the rare earth metal salt in the rare earth metal salt solution is 24:1.
[0018] Preferably, in steps S1 and S2, the molar ratio of the organic ligand to the transition metal salt in the transition metal salt solution is 4-12:1.
[0019] Specifically, in steps S1 and S2, the molar ratio of the organic ligand to the transition metal salt in the transition metal salt solution is 6:1.
[0020] Preferably, in steps S1 and S3, the molar ratio of the organic ligand to the transition metal salt in the transition metal salt solution is 2-6:1.
[0021] Specifically, in steps S1 and S3, the molar ratio of the organic ligand to the transition metal salt in the transition metal salt solution is 3:1.
[0022] Preferably, the solvent of the rare earth metal salt solution is water.
[0023] Preferably, in step S2 or S3, the solvent of the transition metal salt solution is methanol.
[0024] Preferably, in step S1, heating is performed while reflux is performed under stirring conditions.
[0025] Preferably, in step S3, after the reaction is completed, the obtained product is centrifuged, washed and dried.
[0026] Preferably, in step S4, the calcination temperature is 500° C.-800° C., and the holding time is 3 h-8 h.
[0027] Furthermore, the calcination temperature is 600° C. and the calcination time is 5 hours.
[0028] The present invention also provides a rare earth metal-containing porous core-shell nanosphere prepared by the above preparation method.
[0029] Preferably, the particle size of the rare earth metal-containing porous core-shell nanospheres is 300nm-700nm.
[0030] The rare earth metal-containing porous core-shell nanospheres mainly include CeO2 at the core, Co3O4 at the shell, and C, N, O, and Mn elements uniformly distributed in the nanospheres. The prepared rare earth metal-containing multi-component porous core-shell nanospheres exhibit good electrocatalytic performance.
[0031] The present invention also provides a fuel cell, comprising the above-mentioned rare earth metal-containing porous core-shell nanospheres.
[0032] The technical solution of the present invention has the following advantages over the prior art:
[0033] This method uses a one-pot multi-step method for the first time to synthesize trimetallic nanospheres enriched with Ce elements inside and uses them as self-templates for calcination. After calcination, a multi-component porous core-shell nanosphere containing rare earth metals is obtained. Compared with other existing technologies for preparing core-shell structures, the trimetallic coordination polymer synthesized by the one-pot multi-step method in the present invention has a more regular and uniform morphology and size compared with the trimetallic coordination polymer nanospheres synthesized by the one-pot method;
[0034] The present invention synthesizes trimetallic nanospheres through a one-pot multi-step method, in which Ce element enrichment occurs. By using CoCeMn trimetallic coordination polymer as a self-template material, a perfect nanomaterial containing rare earth metals and a multi-component porous core-shell structure can be obtained by simply calcining in an air atmosphere.
[0035] The entire experimental process is green and environmentally friendly, easy to operate, and has a high yield. The prepared composite catalyst has good electrocatalytic oxygen evolution performance and can be used in fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The scanning electron microscope image (I), transmission electron microscope image (II), X-ray powder diffractometer image (III), selected area electron diffraction image (IV) and element mapping image (V) of the CoCeMn coordination polymer synthesized by the one-pot multi-step method prepared in Example 1;
[0037] Figure 2 is a scanning electron microscope image of the CoCeMn coordination polymer synthesized by a one-step method prepared in Example 1;
[0038] Figure 3 The scanning electron microscope image (I), transmission electron microscope image (II), X-ray powder diffractometer image (III), high-resolution transmission electron microscope image (IV), selected area electron diffraction image (V) and element mapping image (VI) of the rare earth metal-containing multi-component porous core-shell nanospheres synthesized by the one-pot multi-step method prepared in Example 2;
[0039] Figure 4 The scanning electron micrograph (I) and transmission electron micrograph (II) of the rare earth metal-containing multi-component porous core-shell nanospheres synthesized by a one-step method prepared in Example 2;
[0040] Figure 5 are the LSV curves of CoCeMn coordination polymer, single metal Co oxide, bimetallic CoMn and CoCe oxide, and rare earth metal-containing multicomponent porous core-shell nanospheres;
[0041] Figure 6 It is the LSV curve of trimetallic oxides with different Ce salt amounts added;
[0042] Figure 7These are the LSV curves of trimetallic oxides with different amounts of Co salt added, trimetallic oxides with different amounts of Mn salt added, and trimetallic oxides synthesized by a one-step method. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0044] Example 1 Synthesis of CoCeMn trimetallic coordination polymer nanospheres
[0045] First, the organic ligand HL was synthesized according to the method of the literature “Convenient Synthesis of Novel Nitrones: (Z)-4-Amino-5-hydroxyimino-2,5-dihydro-1H-imidazole 3-Oxides, Heterocycles, 2009, 78, 1445-1452” 10 , the structure of the organic ligand is as follows:
[0046]
[0047] Then, 0.6 mmol of organic ligand (Z)-4-amino-5-hydroxyoxime-2-(4-n-octyloxyphenyl)-2,5-dihydro-1H-imidazole-3-oxide (HL 10 ) was dissolved in 50 mL of anhydrous methanol solution, heated to 60 °C, and a one-pot multi-step method was used to add 1 mL, 0.025 mmol of cerium acetate aqueous solution for 1 h, 5 mL, 0.1 mmol of manganese acetate methanol solution for 1 h, and 5 mL, 0.2 mmol of cobalt acetate methanol solution for 13 h to synthesize the CoCeMn coordination polymer through a simple coordination reaction.
[0048] Example 2 Preparation of multi-component porous core-shell nanospheres containing rare earth metals
[0049] 0.1 g of the CoCeMn coordination polymer precursor prepared by the one-pot multi-step method in Example 1 was put into a porcelain ark, and the temperature was increased to 600° C. at a heating rate of 1° C. / min in a muffle furnace, and kept at this temperature for 5 h. After the reaction was completed, multi-component porous core-shell nanospheres containing rare earth metals were obtained.
[0050] Example 3
[0051] 0.6 mmol of organic ligand (Z)-4-amino-5-hydroxyoxime-2-(4-n-octyloxyphenyl)-2,5-dihydro-1H-imidazole-3-oxide (HL 10) was dissolved in 50 mL of anhydrous methanol solution, heated to 70 °C, and a coordination polymer was synthesized by a one-pot multi-step method by adding 1 mL, 0.025 mmol of gadolinium acetate aqueous solution for 0.5 h, adding 5 mL, 0.1 mmol of ferrous acetate methanol solution for 0.5 h, and adding 5 mL, 0.2 mmol of copper acetate methanol solution for 12 h.
[0052] 0.1 g of the coordination polymer precursor prepared by the one-pot multi-step method was put into a porcelain ark, heated to 500°C at a heating rate of 1°C / min in a muffle furnace, and kept at this temperature for 8 h. After the reaction was completed, multi-component porous core-shell nanospheres containing rare earth metals were obtained.
[0053] Example 4
[0054] 0.6 mmol of organic ligand (Z)-4-amino-5-hydroxyoxime-2-(4-n-octyloxyphenyl)-2,5-dihydro-1H-imidazole-3-oxide (HL 10 ) was dissolved in 50 mL of anhydrous methanol solution, heated to 60 °C, and a coordination polymer was synthesized by a one-pot multi-step method by adding 1 mL, 0.025 mmol of gadolinium acetate aqueous solution for 2 h, 5 mL, 0.1 mmol of zinc acetate methanol solution for 2 h, and 5 mL, 0.2 mmol of copper acetate methanol solution for 14 h.
[0055] 0.1 g of the coordination polymer precursor prepared by the one-pot multi-step method was put into a porcelain ark, heated to 800°C in a muffle furnace at a heating rate of 1°C / min, and kept at this temperature for 3 h. After the reaction was completed, multi-component porous core-shell nanospheres containing rare earth metals were obtained.
[0056] Comparative Example 1 Synthesis of CoCeMn trimetallic coordination polymer nanospheres
[0057] The same as Example 1, except that a one-pot method is used to gradually add 1 mL, 0.025 mmol cerium acetate aqueous solution, 10 mL, 0.1 mmol manganese acetate and 0.2 mmol cobalt acetate methanol mixed solution, and the other steps remain unchanged, for comparing the difference between the one-pot multi-step method and the one-pot method in obtaining the material.
[0058] Comparative Example 2 Preparation of multi-component porous core-shell nanospheres containing rare earth metals
[0059] 0.1 g of the CoCeMn coordination polymer precursor prepared in Comparative Example 1 was placed in a porcelain ark, heated to 600° C. at a heating rate of 1° C. / min in a muffle furnace, and kept at this temperature for 5 h. The reaction was completed to obtain multi-component porous core-shell nanospheres containing rare earth metals.
[0060] Effect evaluation 1
[0061] Figure 1 In the figure, Ⅰ, Ⅱ, Ⅲ, Ⅳ and Ⅴ are the scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray powder diffractometer (XRD), selected area electron diffraction (SAED) and element mapping (EDX-Mapping) of the CoCeMn coordination polymer synthesized by a one-pot multi-step method. The particle size of the CoCeMn coordination polymer sphere is 1μm-1.5μm, the surface is smooth and the morphology is very uniform. XRD and SAED show that it is an amorphous material. The EDX-Mapping diagram shows that the Ce element is enriched in the nanosphere, which is conducive to the formation of a special core-shell structure after calcination.
[0062] Figure 2 The figure shows a scanning electron microscope (SEM) image of the CoCeMn coordination polymer synthesized in one step. The particle size of the CoCeMn coordination polymer sphere is 600nm-1μm, and the morphology is uneven.
[0063] Figure 3 Ⅰ, Ⅱ, Ⅲ, Ⅳ, Ⅴ and Ⅵ are the scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray powder diffractometer (XRD), high-resolution transmission electron microscope (HRTEM), selected area electron diffraction (SAED) and element mapping (EDX-Mapping) of the multi-component Co3O4 / CeO2 porous core-shell nanomaterials synthesized by a one-pot multi-step method. The results of SEM and TEM images show that the original solid spheres of about 1um have become porous core-shell nanospheres of about 500nm with uniform morphology. XRD, HRTEM and SAED images show that the main substances are Co3O4 and CeO2. In addition, it can be easily seen from the EDX-Mapping image that a multi-component Co3O4 and CeO2 core-shell structure has been formed.
[0064] Figure 4 Figures Ⅰ and Ⅱ are scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images of multi-component porous core-shell nanospheres containing rare earth metals synthesized by one-step method, respectively. The results of SEM and TEM images show that the nanospheres synthesized by one-step method are still not uniform after calcination, and there is no very obvious core-shell structure, which may be because the one-step synthesis affects the distribution of metal elements in the CoCeMn trimetallic coordination polymer, resulting in no element enrichment inside it.
[0065] Effect evaluation 2
[0066] The hollow nanomaterial prepared in the present invention can be used as an electrocatalytic oxygen evolution catalyst. Figure 5 In the figure are the LSV curves of CoCeMn coordination polymer, single metal Co oxide, bimetallic CoMn and CoCe oxide and multicomponent porous core-shell nanospheres containing rare earth metals; Figure 6The middle ones are LSV curves of three metal oxides with different Ce salt amounts added; Figure 7 The figures in the figure show the LSV curves of trimetal oxides with different amounts of Co salt, trimetal oxides with different amounts of Mn salt and trimetal oxides synthesized by one-step method. Among them, the multi-component porous core-shell nanospheres containing rare earth metals all show the best electrocatalytic oxygen evolution performance (OER), which may be attributed to their special porous core-shell structure and the synergistic effect between multiple components.
[0067] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A fuel cell, characterized in that: The invention comprises porous core-shell nanospheres containing rare earth metals; and the preparation method of the porous core-shell nanospheres containing rare earth metals comprises the following steps: S1: After dissolving the organic ligand, heat to 60°C-70°C, add the rare earth metal salt solution, and react for 0.5 h-2 h to obtain a primary reaction solution; the structural formula of the organic ligand is as follows: ; S2: adding a transition metal salt solution to the primary reaction solution and reacting for 0.5 h-2 h to obtain a secondary reaction solution; S3: adding a transition metal salt solution to the secondary reaction solution and reacting for 12 h-14 h to obtain a tertiary reaction solution; S4: centrifuging and drying the three reaction solutions and then calcining them to obtain the rare earth metal-containing porous core-shell nanospheres; the rare earth metal salt in the rare earth metal salt solution is cerium acetate or gadolinium acetate; in step S2 or S3, the transition metal salt in the transition metal salt solution is one or more of ferrous acetate, cupric acetate, manganese acetate, zinc acetate and cobalt acetate.
2. The preparation method according to claim 1, characterized in that The molar ratio of the organic ligand to the rare earth metal salt in the rare earth metal salt solution is 3-36:
1.
3. The preparation method according to claim 1, characterized in that: In the steps S1 and S2, the molar ratio of the organic ligand to the transition metal salt in the transition metal salt solution is 4-12:
1.
4. The preparation method according to claim 1, characterized in that: In the steps S1 and S3, the molar ratio of the organic ligand to the transition metal salt in the transition metal salt solution is 2-6:
1.
5. The preparation method according to claim 1, characterized in that: In the step S2 or S3, the solvent of the transition metal salt solution is methanol.
6. The preparation method according to claim 1, characterized in that: In the step S4, the calcination temperature is 500° C.-800° C., and the holding time is 3 h-8 h.
7. A rare earth metal-containing porous core-shell nanosphere prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Multi-layer core shell structure CeO2 nanometer hollow sphere template-free composite method
CN104925845A
Cerium-based composite oxide VOCs (volatile organic compounds) combustion catalyst using metal organic framework as template and preparation method thereof
CN107983329A